2014
DOI: 10.4236/ojped.2014.43025
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Upper GI Endoscopy in Pediatric Population at a Tertiary Care Centre in Pakistan

Abstract: Although upper GI endoscopy is considered to be a gold standard in diagnosis of many pediatric gastrointestinal disorders, there is limited data about its utility from developing countries. We carried out this retrospective study at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 10 publications
4
15
0
Order By: Relevance
“…Esophageal varices was the most common endoscopic finding in the present study, seen in 49% of children. Recent report by Khan, et al 11 have shown esophageal varices in only 5% of paediatric upper GI endoscopy. Our result is far away from this because of referral bias which has already been mentioned above.…”
Section: Resultsmentioning
confidence: 95%
“…Esophageal varices was the most common endoscopic finding in the present study, seen in 49% of children. Recent report by Khan, et al 11 have shown esophageal varices in only 5% of paediatric upper GI endoscopy. Our result is far away from this because of referral bias which has already been mentioned above.…”
Section: Resultsmentioning
confidence: 95%
“…Endoscopic findings in children do not appear to be documented in many paediatric endoscopic studies. [2,[5][6][7][10][11][12][13] In terms of endoscopic findings, 15.5% of our subjects had normal studies while the most common finding was gastritis (25.3%). Studies done in Pakistan, Saudi Arabia and Colombia have also reported similar findings.…”
Section: Discussionmentioning
confidence: 99%
“…[6] In Uganda, gastritis and duodenal ulcers were found to be the most common endoscopic findings. [7] There is a dearth of information on the utility of the procedure in children, especially in the West African sub-region. Therefore, this study was carried out to outline the indications and the spectrum of endoscopic diagnosis in children seen at the Lagos University Teaching Hospital (LUTH).…”
mentioning
confidence: 99%
“…Similar fi gures are reported in other developing countries 11,12 . Studies from specialized gastroenterology centre or developed world however report much lower propor ons of children undergoing endoscopy primarily for abdominal pain 6 .…”
Section: Discussionmentioning
confidence: 99%
“…In the developing world however, use of gastrointes nal endoscope in paediatrics is s ll in infancy. Lack of awareness of its applica on, limited paediatric friendly endoscopy suites/endoscopes and lack of adequately trained physicians who can safely perform the procedure are the greatest hurdles 6,7 . Paediatric gastroenterology services have just started to be recognized as important subspecialty in Nepal and we are s ll far from u liza on of technical advance with this procedure.…”
Section: Introductionmentioning
confidence: 99%